Assessment of the ecological quality of soft-bottom benthic communities in the Syrian coast, Eastern Mediterranean - Ammar , I.; Hussein, Ch. (Mesopotamian Journal of Marine Sciences, 2022)
The present study was aimed to evaluate several benthic biological indices to assess the ecological quality status of marine environments in Syria. Samples were obtained from four different areas of Syrian coast (Al-Bassit, Banias, Tartous and Al-Hamidia) on a monthly scale from March 2007 to December 2007. Results showed that the percentage of benthic species are increased significantly in the stations with healthy ecological status. The cluster analysis and the MDS have shown that the studied stations are subjected to environmental disturbance. Some species have been found to be more sensitive (high values of Hurlbert Index) than others such as the Rhinoclavis kochi, which belonged to the Gastropodes taxa and Notomastus latericeus belonged to the polychaetes taxa. The ecological quality of the Syrian coast was assessed using three biotic indices (H′, AMBI and BQI). The Shannon–Wiener index H′ was ranged from 2.88 to 5.39. Thus, the ecological status varied between moderate and high. The values of AZTI Marine Biotic Index (AMBI) and Benthic Quality Index (BQI) classified the ecological state between high and good (slight disturbance).